2015
DOI: 10.18036/btdc.61431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenously Applied Spermine and Putrescine on Germination and in Vitro Growth of Pepper (Capsicum Annuum L.) Seeds Under Salt Stress

Abstract: Plant growth regulators play a significant role in germination of seed. In this study, Effects of exogenous polyamines (spermine and putrescine) on germination of seed and seedling growth such as radicula length, hypocotile length, fresh weight, dry weight of pepper under salt stress were investigated. According to results, increased salt concentration resulted in a significant reduction in germination (P<0.05). NaCl prevented hypocotile growth and this inhibition was reversed by applying spermine. During appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
1
0
4
Order By: Relevance
“…In the 1.0 Put application, in which putrescine was used alone without salt stress, higher results in terms of germination properties were obtained compared with the control (Table 2). Similar to the results obtained in this study, negative effects of salt stress on germination have been reported in previous studies on different vegetables (Dadaşoğlu and Ekinci, 2013;Koç et al, 2014;Mena et al, 2015;Mohamedsrajaden, 2019;Kibar et al, 2020). It was determined that putrescine application alone without salt stress increased the germination rate, radicle and plumule length in pepper compared to the control, and putrescine was more effective especially at low concentrations (Khan et al, 2012).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the 1.0 Put application, in which putrescine was used alone without salt stress, higher results in terms of germination properties were obtained compared with the control (Table 2). Similar to the results obtained in this study, negative effects of salt stress on germination have been reported in previous studies on different vegetables (Dadaşoğlu and Ekinci, 2013;Koç et al, 2014;Mena et al, 2015;Mohamedsrajaden, 2019;Kibar et al, 2020). It was determined that putrescine application alone without salt stress increased the germination rate, radicle and plumule length in pepper compared to the control, and putrescine was more effective especially at low concentrations (Khan et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…In the study carried out by Zeid (2004) on bean, germination rate increased with the external putrescine application under salty conditions. Likewise, in studies conducted in pepper (Koç et al, 2014), tomato (Mohamedsrajaden, 2019), fresh bean (Kibar et al, 2020) and pumpkin (Farsaraei et al, 2021), it was stated that salinity negatively affected germination and the harmful effects of salt stress on germination parameters can be reduced with putrescine application. Ekinci et al (2011) reported that the highest germination rate was obtained from 0.50 mM salicylic acid application in parsley, lettuce and carrot seeds, and 0.1 mM salicylic acid application in cabbage seeds, and that high doses of salicylic acid reduced the germination rate of seeds.…”
Section: Resultsmentioning
confidence: 99%
“…La fenilalanina amonio liasa (PAL, EC 4.3.1.5) es una enzima clave involucrada tanto en el primer paso de la vía de fenilpropanoides que convierte la L-fenilalanina en ácido transcinámico 52 , como en la biosíntesis de fenoles, conduciendo principalmente a la producción de lignina en las células vegetales. La actividad de PAL puede aumentar en raíces, hojas y tallos de plantas resistentes de Capsicum a los 2 o 3 DPI con P. capsici 16,53 . Inclusive se ha comprobado un aumento de los niveles de compuestos fenólicos y de la actividad enzimática de su precursor PAL (figura 5) al sexto DPI con el oomiceto 49,54 .…”
Section: Fenilalanina Amonio Liasaunclassified
“…Otra enzima como CAT puede aumentar su actividad en plantas resistentes en comparación a las susceptibles, tanto al inicio de la infección, como hasta los siete DPI con altas concentraciones de inoculo de P. capsici, limitando la excesiva producción de H 2 O 2 y la peroxidación lipídica 16 . Esto hace que se evite el estrés oxidativo en la planta y la muerte celular innecesaria por la degradación de la mem-brana plasmática, gracias a la actividad de enzimas como CAT y POX (Figura 5) 20,54 .…”
Section: Regulación De La Muerte Celular Y Especies Reactivas De Oxígenounclassified
See 1 more Smart Citation